The applied mechanical equipments for wastewater treatment in the észak-Alföld region - Szőllősi, István; Antal, Tamás; Uri, Zsuzsanna; Simon, László; Szilágyi, Attila (Acta Agraria Debreceniensis, 2017)
In this study we presented the results of a survey research, which was performed during 2015 at 34 sewage treatment works, operating in Észak-alföld region (Hungary). The survey focused on applied mechanical equipment and works of art of the sewage treatment establishments. The results of the survey showed that the majority of the examined sites (approx 65%) are working with capacity utilization of 50–100%,merely the 12% of plants was overload. It was found analyzing of specific energy consumption of the sites that the largest value (1.1 kWh per m3) was at the plants with smaller capacity (0–1000 m3 per day). It was clear during the questionnaire processing of the survey that almost all of the works applied activated sludge for sewage treatment The sludge treatment of the sewage plants is conducted by two methods; aerobic- and mixed (anaerobic and aerobic) sludge stabilization. We suggest for the plants with small capacity to use deep aerators, since anachronistic method used the at 3% of the settlements.